Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD

Humidity-sensing studies of cerium oxide nanoparticles synthesizedby non-isothermal precipitation - Khadse, V. R.; Thakur, Sharada; Patil, K. R.; Patil, Pradip (Sensors and Actuators B-Chemical, 2014)
We report the fabrication of a highly sensitive and fast humidity sensor based on cerium oxide (CeO2) nanoparticles, which were prepared at low cost via a simple non-isothermal precipitation method. The asprepared CeO2 nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy( TEM) and the results indicated the formation of face centered cubic phase of CeO2 with average crystallite size of approximately 10-12 nm. Humidity sensors based on CeO2 nanoparticles exhibit high and linear response within the whole relative humidity (RH) range of 11-97% at an operating frequency of 60 Hz. The corresponding impedance changes by approximately three orders of magnitude within the entire humidity range from 11% to 97% RH. The response and recovery times are about 2-3 and 9-10 s, respectively, when RH was switched between 11% and 97%. Furthermore, the sensors also show relatively small hysteresis, excellent reproducibility, long term stability and broad range of operation (11-97% RH). The complex impedance spectra of the sensor at different RHs and the equivalent circuit were analyzed to explore the humidity-sensing mechanism. This study demonstrates that the CeO2 nanoparticles prepared by non-precipitation method can be used as the humidity-sensing material for the fabrication of humidity sensors. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: CeO2 nanoparticles; Complex impedance spectra; humidity sensor; Non-isothermal precipitation; TEM